Passages - Lackey, Mercedes; English, Charlotte E.; Sharp, Anthea; Brozek, Jennifer, 1970-; Waters, Elisabeth; Schwengel, Kristin; Vaughan, Elizabeth (Elizabeth A.); Dermatis, Dayle A.; Christie, Paige L.; Swann, Louisa; Lang, Michele; Collins, Brigid (Fantasy fiction writer); et al. (DAW book collectors, 2020)
In this fourteenth anthology of short stories set in the beloved Valdemar universe, the Heralds of Valdemar, the kingdom's ancient order of protectors, protect the peace, ride throughout the kingdom, defending their land and monarch.